Inovasi Zea Coffee Tab Berbasis Robusta dan Rambut Jagung sebagai Minuman Fungsional untuk Remaja Overweight - Intan Afita Khoirun Nisa; Efina Amanda; Mulya Agustina (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Nutritional problems among adolescents are increasingly associated with unhealthy dietary habits and low physical activity, contributing to the rising prevalence of overweight. According to the 2023 Indonesian Health Survey, overweight prevalence among adolescents ranges from 12% to 16.2%. This study aimed to develop Zea Coffee Tab, a functional beverage made from Robusta coffee and corn silk containing bioactive compounds, including caffeine and flavonoids, which may support metabolism and body fat oxidation. An experimental method with a Completely Randomized Design (CRD) was employed. The evaluated parameters included organoleptic tests (hedonic and hedonic quality) involving 30 semi-trained panelists, proximate analysis, and identification of bioactive compounds. Data were analyzed using the Kruskal–Wallis, Mann–Whitney, One-Way ANOVA, and Duncan’s multiple range tests. Three formulations were tested: F1 (30% Robusta coffee:70% corn silk), F2 (50%:50%), and F3 (70%:30%). The findings showed that F3 was the most preferred formulation, with an acceptance score categorized as “very much liked.” The product contained energy ranging from 319.20–324.26 kcal/100 g, protein 5.12–5.34%, fat 0.48–0.58%, carbohydrates 73.85–74.51%, moisture 9.12–9.66%, ash 2.10–2.32%, caffeine 182.45–205.86 mg/100 g, and flavonoids 4.28–6.03 mg/100 g. Zea Coffee Tab has the potential to serve as a healthy functional beverage for overweight adolescents. Further studies on shelf life and clinical effectiveness are recommended to support product commercialization.